Balancing Innovation and Ethics: The Impact of AI Integration on Educational Leadership Outcomes - Zohaib Hassan Sain; Uthman Shehu Lawal; Chanda Chansa Thelma; Shahzadi Hina Sain (Didaktika: Jurnal Kependidikan, 2024)
This study investigates the integration of Artificial Intelligence (AI) in educational leadership, emphasizing the balance between maximizing AI’s benefits and managing its ethical responsibilities. The research aims to analyze how managing AI’s benefits, such as administrative efficiency (84% agreement) and data-driven decision-making (75% agreement), along with addressing ethical risks, including privacy concerns (85% agreement) and accountability (82% agreement), impacts institutional outcomes. Employing a mixed-methods approach, quantitative data from 150 survey responses were analyzed through descriptive statistics, correlation, and regression analyses, revealing positive correlations between AI management and institutional outcomes (e.g., r = 0.68 for administrative efficiency). Qualitative data from 20 interviews were analyzed thematically, with prominent themes including privacy, fairness, and transparency. The quantitative data showed that effective AI management is significantly associated with improved institutional outcomes, while qualitative insights underscored the need for ethical frameworks to guide AI use. Balancing AI’s operational benefits with ethical safeguards enhances institutional effectiveness and supports responsible AI integration in educational settings. These findings provide a foundation for policies that promote transparency, accountability, and fairness in AI-driven educational leadership.